2018
DOI: 10.1097/mao.0000000000001892
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Crossover Study in Single Sided Deafness on the New Non-Invasive Adhesive Bone Conduction Hearing System

Abstract: To the best of our knowledge, this is the first study to report on the outcomes of the new adhesive system. Users' satisfaction of the adhesive hearing system was found to be comparable to the control device. Since the hearing outcomes vary highly between patients, trials with applicable hearing systems are recommended in SSD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…Our results signifying substantial neuroplasticity in regions of the auditory cortex of unilaterally deafened people indicate that early intervention is needed to protect from maladaptive reorganization caused by asymmetric input. Intervention can include (re)activating the deaf ear using appropriate hearingassistive devices such as a bone-anchored hearing aid or CI for profound hearing loss (Dorman et al, 2016;Laszig et al, 2017;Mertens et al, 2018). It has also been claimed that restoration of binaural hearing with a CI actually improves the speech-in-noise and sound localization capabilities of unilateral deaf individuals regardless of the deafened side (Ehrmann-mueller et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our results signifying substantial neuroplasticity in regions of the auditory cortex of unilaterally deafened people indicate that early intervention is needed to protect from maladaptive reorganization caused by asymmetric input. Intervention can include (re)activating the deaf ear using appropriate hearingassistive devices such as a bone-anchored hearing aid or CI for profound hearing loss (Dorman et al, 2016;Laszig et al, 2017;Mertens et al, 2018). It has also been claimed that restoration of binaural hearing with a CI actually improves the speech-in-noise and sound localization capabilities of unilateral deaf individuals regardless of the deafened side (Ehrmann-mueller et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Griet Mertens et al compared the performance of CROS and ADHEAR in 17 SSD patients. Although many participants preferred ADHEAR in this study, speech perception in the noise condition showed that only CROS improved significantly in the HL S NH N condition.…”
Section: Discussionmentioning
confidence: 99%
“…Dahm et al estimated an average battery durability of 5.9 days [11], but as stated by Neumann et al, excessive handling of the adapter, mastoid shape, skin type, and sweating could cause variation [14]. As stated by Mertens et al, for optimal retention of the adhesive adapter, special attention should be paid to the skin preparation (clean and dry) and correct placement [18].…”
Section: Discussionmentioning
confidence: 99%